2022
DOI: 10.21037/jgo-22-624
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of gemcitabine-based combination therapy vs. gemcitabine alone for the treatment of advanced pancreatic cancer: a systematic review and meta-analysis

Abstract: Background: Gemcitabine (GEM) is used as a standard first-line drug to effectively alleviate symptoms and prolong survival time for advanced pancreatic cancer. Most randomized controlled trials (RCTs) show that GEM-based combination therapy is better than GEM alone, while some RCTs have the opposite conclusion. This study aimed to investigate whether GEM-based combination therapy would be superior to GEM alone by a systematic review and meta-analysis.Methods: According to the PICOS principles, RCTs (S) focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…More than 10% of the patients who receive GEM develop severe adverse effects, such as low white and red blood cell counts, and low platelet counts due to bone marrow suppression. Other common side effects associated with GEM administration include vomiting and nausea, difficulty breathing, rashes and itchy skin, hair loss, flu-like symptoms, edema, fever, loss of appetite (which can contribute to the development of cancer cachexia), headaches, difficulty sleeping, fatigue, and many others that significantly decrease the quality of life of patients [ 16 ]. In a case study, Mascherona et al [ 17 ] reported the development of clinically significant acute hepatic injury after using gemcitabine in a 73-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…More than 10% of the patients who receive GEM develop severe adverse effects, such as low white and red blood cell counts, and low platelet counts due to bone marrow suppression. Other common side effects associated with GEM administration include vomiting and nausea, difficulty breathing, rashes and itchy skin, hair loss, flu-like symptoms, edema, fever, loss of appetite (which can contribute to the development of cancer cachexia), headaches, difficulty sleeping, fatigue, and many others that significantly decrease the quality of life of patients [ 16 ]. In a case study, Mascherona et al [ 17 ] reported the development of clinically significant acute hepatic injury after using gemcitabine in a 73-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…Near 80%-90% of patients who suffered from PDAC had unresectable tumors or metastatic disease at the time of the first diagnosis, with a 5-year overall survival (OS) rate of 10%, despite the development of the radical surgical treatment. Although gemcitabine is a recognized first-line chemotherapy drug for PDAC, it is still unclear whether there is an advantage for survival (Zhang et al, 2022). Therefore, new cancer treatments are urgently needed for the treatment of metastatic or incurable PDAC (Von Hoff et al, 2013;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine (2′,2′-Difluoro-2′-deoxycytidine) is the most commonly prescribed chemotherapeutic agent for pancreatic cancer [ 12 ]. An analog of deoxycytidine, gemcitabine is a pro-drug [ 13 ].…”
Section: Introductionmentioning
confidence: 99%